Leveraging chorionic villus biopsies for the derivation of patient-specific trophoblast stem cells - Kaela M. Varberg; Ayelen Moreno-Irusta; Allynson Novoa; Brynne Musser; Joseph M. Varberg; Jeremy P. Goering; Irfan Saadi; Khursheed Iqbal; Hiroaki Okae; Takahiro Arima; John Williams; Margareta D. Pisarska; et al. (Communications Biology)
Abstract Human trophoblast stem (TS) cells are informative in vitro models for the generation and testing of biologically meaningful hypotheses. The goal of this project was to derive patient-specific TS cell lines from clinically available chorionic villus biopsies. Cell outgrowths were captured from human chorionic villus tissue specimens cultured in modified human TS cell medium. Cell colonies emerged early during the culture and cell lines were established and passaged for several generations. Karyotypes of the newly established chorionic villus-derived trophoblast stem (TSCV) cell lines were determined and compared to initial genetic diagnoses from freshly isolated chorionic villi. Phenotypes of TSCV cells in the stem state and following differentiation were compared to cytotrophoblast-derived TS (TSCT) cells. TSCV and TSCT cells uniformly exhibited similarities in the stem state and following differentiation into syncytiotrophoblast and extravillous trophoblast cells. Chorionic villus tissue specimens provide a valuable source for TS cell derivation. They expand the genetic diversity of available TS cells and are associated with defined clinical outcomes. TSCV cell lines provide a new set of experimental tools for investigating trophoblast cell lineage development.